Sistem Mobile Deteksi Gangguan Kejiwaan Berbasis Suara Menggunakan Metode Deep Convolutional Neural Network - Nugroho, Kristiawan; Jusran, Alek; Sari, Linda Kartika; Nofiyanto, Muhamat; Suprihhartini, Suprihhartini (Jurnal Sains dan Teknologi Informasi, 2025)
-Mental disorders are a global health problem that often goes undetected early, requiring innovative approaches to their detection. This study aims to develop a mobile system capable of detecting mental disorders based on voice using Deep Convolutional Neural Network technology. The method used in this study is the collection of voice data from individuals experiencing symptoms of mental disorders, followed by voice feature extraction and the application of a Deep Convolutional Neural Network model for the classification of these disorders. The system was tested using a processed voice dataset, which includes various types of mental disorders, including depression and anxiety. The results showed that the Deep Convolutional Neural Network model was able to achieve high detection accuracy, with the ability to recognize mental disorders based on specific voice characteristics. This finding opens new opportunities for faster and more efficient detection of mental disorders using mobile devices, which are accessible to the wider community. This study also demonstrates the great potential of deep learning technology in the field of mental health, particularly in the prevention and diagnosis of mental disorders.